1975
DOI: 10.1210/jcem-40-3-478
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adrenergic Stimuli in Parathyroid Hormone Secretion in Man

Abstract: The role of adrenergic stimuli in the secretion of parathyroid hormone (PTH) in man was evaluated. Intradermal injections of isoproterenol, 0.15 mg, or epinephrine, 0.3 mg, caused significant prompt increases in serum PTH levels. These increases were not accompanied by any changes in serum calcium (Ca) during the period of observation. Phenylephrine, 1.5 mg, intradermally, did not cause any significant changes in serum PTH or serum Ca. Propranolol infusion alone significantly inhibited the basal secretion of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
3

Year Published

1976
1976
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(61 citation statements)
references
References 0 publications
8
50
3
Order By: Relevance
“…Fischer et al (18) have recently demonstrated that PTH release can be induced in cows by the infusion of epinephrine, and that this effect is mediated through a , 8 adrenergic receptor mechanism. Similar results have been obtained in human subjects (24). Also, it is well established that the parathyroid glands are encanvassed by a dense network of sympathetic nerve fibers (1, 51).…”
Section: Discussionsupporting
confidence: 85%
“…Fischer et al (18) have recently demonstrated that PTH release can be induced in cows by the infusion of epinephrine, and that this effect is mediated through a , 8 adrenergic receptor mechanism. Similar results have been obtained in human subjects (24). Also, it is well established that the parathyroid glands are encanvassed by a dense network of sympathetic nerve fibers (1, 51).…”
Section: Discussionsupporting
confidence: 85%
“…In addition, it is known that PTH synthesis is also stimulated by b adrenergic agonists and though we cannot rule out such a mechanism, it has been pointed out that this is a minor effect physiologically compared the effect produced by ionized calcium [23].…”
Section: Discussionmentioning
confidence: 85%
“…It can be speculated that parathyroid hormone (PTH) which has a more direct effect on level of ionized calcium is also perturbed by elevated lead levels [23]. It indicates that lead is an endocrine modulator and can thus be responsible for endocrinal disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that catecholamines stimulate CT and PTH secretion both in rats (Hsu & Cooper 1975) and humans (Vora et at. 1978, Kukreja et al 1975), possibly through activation of adrenergic p2 receptors (Fournier et al 1979). As secretion of catecholamines increases following trauma (Kiyomi & Brooks 1974), this may have influenced both the CT and PTH secretion in the present study.…”
Section: Discussionmentioning
confidence: 99%